Geology and stream sediment geochemistry of the Vilyuchinsky gold district, Southern Kamchatka, Russian Federation. (4th July 2015) - Abzalov, M. Z.; Shadrin, A.
Abstract : The Kamchatka–Kuril island arc forms the northeastern margin of the Eurasian continent, including the Kuril Islands, Kamchatka Peninsula and parts of the Koryak Highlands. This composite island arc, over 2000 km long, contains abundant epithermal gold deposits with total resources currently assessed at approximately 30 Moz of gold. Epithermal gold deposits of the Kamchatka–Kuril arc cluster in several gold districts associated with Neogene volcanism, Koryak, Northern Kamchatka, Central Kamchatka, Kumroch and Southern Kamchatka (Vilyuchinsky), and there are also smaller deposits in the Kuril Islands. The Vilyuchinsky district comprises mainly intermediate and felsic volcanic rocks of Miocene and Pliocene age overlying a sedimentary flysch sequence, and locally overlain by Quaternary basalts. Shallow subvolcanic intrusions represent the roots of Neogene palaeovolcanic structures that were exposed by erosion. Epithermal gold deposits in the Vilyuchinsky district are of the adularia-sericite type and form north west trending linear arrays that are spatially associated with the Vilyuchinsky crustal fault that bounds the district to the North. Mineralisation is spatially associated with, and is commonly hosted by, subvolcanic intrusions of dacite and andesitic-dacite exposed in the deeply eroded palaeovolcanic centres. The Vilyuchinsky district was mapped and explored at a scale of 1 : 50 000. All creeks were systematically sampled at a density of approximately one sample per 500 m along the stream infilled to 1 : 25 000 in geologically favourable areas. Analysis of stream sediment assays indicates that gold has a multi-modal statistical distribution, suggesting the presence of different levels of geochemical anomalies. Gold assays ≥ 20 ppb are classified as anomalous, and values ≥ 100 ppb are classified as highly anomalous. In the Kamchatka region, deposits containing more than 1 Moz of gold coincide with stream sediments that contain ≥ 100 ppb of gold. In the Vilyuchinsky district, such samples are found only around the Porozhistoe deposit. Copper and lead values in stream sediments are classified as anomalous at ≥ 100 ppb and ≥ 30 ppb, respectively. Base metals and gold are commonly distributed in three separate zones surrounding diorite porphyry centres (e.g. at the Balaganchik prospect). Copper anomalies occur in the vicinity of diorite porphyry intrusions, lead is present 2–3 km from the centres, forming an intermediate geochemical halo, and gold veins and related stream sediment anomalies form an outer halo most distant, commonly >5 km from the diorite centres. The zoned nature of the stream sediment anomalies can be used as a geochemical vector to facilitate exploration.